2006
DOI: 10.1093/humrep/del020
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of combined metformin–letrozole in comparison with metformin–clomiphene citrate in clomiphene-resistant infertile women with polycystic ovarian disease

Abstract: In clomiphene-resistant PCOS patients, the combination of letrozole and metformin leads to higher full-term pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 12 publications
4
48
1
1
Order By: Relevance
“…This finding is in line with the results obtained by Mitwally et al [20] and Sohrabvand et al [21]. It is probable that the cause of endometrial thickening in patients receiving letrozole is because of improved vascularization as compared with clomiphene citrate [22].Another study also showed that clomiphene citrate can cause inadequate endometrial thickness in 15-50% of patients and have negative effects on the quality or quality of the cervical and endometrial mucosa [22].These complications may be attributed to the anti-estrogenic effect and the relatively longer half-life of clomiphene citrate [11].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with the results obtained by Mitwally et al [20] and Sohrabvand et al [21]. It is probable that the cause of endometrial thickening in patients receiving letrozole is because of improved vascularization as compared with clomiphene citrate [22].Another study also showed that clomiphene citrate can cause inadequate endometrial thickness in 15-50% of patients and have negative effects on the quality or quality of the cervical and endometrial mucosa [22].These complications may be attributed to the anti-estrogenic effect and the relatively longer half-life of clomiphene citrate [11].…”
Section: Discussionsupporting
confidence: 93%
“…In a study by Khadem et al, the use of Clomiphene with ethinyl estradiol had a significant effect on endometrial thickness than those who had used Clomiphene alone, but had not been effective on the pregnancy rate and abortion [17]. However in a study by Sohrabvand et al, favourable changes were not observed from treatment with ethinyl estradiol [18]. Therefore, another drug called Letrozole (an Aromatas inhibitor) which is effective for the treatment of patients resistant to Clomiphene has been taken into consideration [19].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a prospective open-labeled randomized controlled trial was conducted to determine which regime, Clomiphene citrate or Letrozole, was the best ovulation induction agent in infertile women with PCOS. Inclusion criteria were an age between 18 years and 40 years old, diagnosed with PCOS by the Rotterdam criteria (2003) and normal seminal fluid analysis (SFA) [5]. Patients were not illiterate and consented to participate in the study.…”
Section: Introductionmentioning
confidence: 99%